If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + 7) = 4x + -7 Reorder the terms: -2(7 + x) = 4x + -7 (7 * -2 + x * -2) = 4x + -7 (-14 + -2x) = 4x + -7 Reorder the terms: -14 + -2x = -7 + 4x Solving -14 + -2x = -7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -14 + -2x + -4x = -7 + 4x + -4x Combine like terms: -2x + -4x = -6x -14 + -6x = -7 + 4x + -4x Combine like terms: 4x + -4x = 0 -14 + -6x = -7 + 0 -14 + -6x = -7 Add '14' to each side of the equation. -14 + 14 + -6x = -7 + 14 Combine like terms: -14 + 14 = 0 0 + -6x = -7 + 14 -6x = -7 + 14 Combine like terms: -7 + 14 = 7 -6x = 7 Divide each side by '-6'. x = -1.166666667 Simplifying x = -1.166666667
| -4=13.7 | | 15-3x=12-5x | | 4w(w-6)-2w^2=2w^2+8w-4 | | 2+3n=0.8n+18 | | 14-x=3x-2 | | x^3+5x^2+16x+80=0 | | 4/28=x/147 | | -7(x-6)-8=-5x+40 | | 5W+W=36 | | h=9(8m-9r) | | 6(-6-5)-6=0 | | ln(x+11)+ln(x-3)=2lnx | | 0=a^2-18a+72 | | 4x+6=-7x-7 | | -15t^2+60t=0 | | 5t+6-8t=30 | | 24t^2+19t+2=0 | | .25p+7=3 | | (2x^2-5x-3)=0 | | 2q+30=6-4q | | 50x=20x+10 | | 3x+5+6x=113 | | 50x=20x+30 | | x-2+25=66-2+3x | | 6p-2(p+6)=20 | | 0.5d-8=3 | | -4b+40=-4(2b-5) | | -10-0.5x=-27.5 | | x-2+25=66-2+x | | 5d+6=3d+16 | | 3x^2+18x-10=0 | | 8(x-8)=-45.6 |